Technology Integration in Predicting Financial Performance: Big Data, Intellectual Capital, and Board Diversity - Aprianti, Siska; Sandrayati, Sandrayati; Sari, Kartika Rachma (Eastasouth Institute, 2024)
The relationship between technological integration, diversity on the board, and intellectual capital management and how these factors affect the financial performance of Indonesian start-ups is examined in this study. Structural Equation Modeling (SEM) using Partial Least Squares (PLS) approach is used in this work to evaluate the intricate interactions among these critical parameters using a diverse sample of 195 start-ups. A thorough knowledge of the dynamics that influence startups' financial success is facilitated by the use of descriptive statistics, measurement model assessment, and structural model analysis. The findings indicate that there are strong positive correlations between financial performance and board diversity, intellectual capital, and technological integration. Furthermore, the mechanisms involved are clarified by mediation effects. The model explains half of the variance in financial performance (R2 = 0.504) and demonstrates strong predictive relevance (Q2 = 0.354). For practitioners, politicians, and investors navigating Indonesia's competitive start-up entrepreneurship scene, the findings provide insightful information.